Dietary patterns and nutritional status of Polish elite athletes - Tyrala, F.; Fraczek, B. (Nutrients, 2025)
Background: Rational dietary patterns and adequate nutritional status support athlete health and performance, while unhealthy habits may impair these outcomes. This study aimed to identify dietary patterns among Polish professional athletes using a food frequency questionnaire and assess their correlations with nutritional status indicators.